PENGARUH KINERJA GURU BERSERTIFIKAT PROFESI TERHADAP HASIL PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PEMINATAN KEJURUAN - Sinta Sintia, - (2020)
The teacher certification program is one of the government programs that aims to improve teacher performance in carrying out their teaching assignments. Improved teacher performance, is expected to improve student achievement outcomes. This study aims to determine the general picture of professional certified teachers performance, the result of student achievement, and to find out the influence of professional certified teachers performance on the results of student achivement in the vocational learning in SMK Negeri 1 Sumedang. The research method used is the Ekspalantory Research method with a quantitative approach. The number of research samples as many as seven (7) teachers specializing in vocational learning in building design and information design competencies (DPIB) who have passed professional certification. A teacher performance assesments is based on student perspectives include a teacher pedagogical abilities in planning, implementing, and evaluating learning. Certified teachers performance data was collected through a questionnaire, while student achievement results were obtained through documentation. The results showed that the average of professional certified teachers performance was in good category, the average result of student achievement was in good category, and there is a positive and significant influence between the professional certified teachers performance on student learning outcomes with a value of τ ̂ count = 0.905> τ table = 0.714 with an effective influence of 26%. The 26% result shows that the teacher's performance in the pedagogical aspect, while there are many other aspects that are not included in the research. Several studies stated that the certification program had not had a significant impact on teacher performance. In terms of certification, the program had to be viewed from various aspects in detail, not only from the learning aspect.